2021
DOI: 10.1016/j.nicl.2021.102704
|View full text |Cite
|
Sign up to set email alerts
|

Resting state prefrontal cortex oxygenation in adolescent non-suicidal self-injury – A near-infrared spectroscopy study

Abstract: Highlights Resting prefrontal cortex (PFC) oxygenation is decreased in adolescents with non-suicidal self-injury (NSSI) compared to healthy controls. Lower PFC oxygenation (full sample) is associated with greater adverse childhood experiences and less health-related quality of life (HRQoL). On the group-level, patients show no alterations of resting state functional connectivity within the PFC. Among other clinical variables, increased P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…The reason false alarms exist is that the data collected could not give a full view of high-suicide-risk students. False alarms remind us to include more aim indicators in data collection, such as impulsivity, near-infrared spectroscopy (NIRS), electroencephalogram (EEG), and some genetic indices ( Lutz et al, 2017 ; Hirose et al, 2018 ; Costanza et al, 2021 ; Iznak et al, 2021 ; Koenig et al, 2021 ). Lifetime SA was significantly associated with both higher impulsivity and higher aggression ( Costanza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason false alarms exist is that the data collected could not give a full view of high-suicide-risk students. False alarms remind us to include more aim indicators in data collection, such as impulsivity, near-infrared spectroscopy (NIRS), electroencephalogram (EEG), and some genetic indices ( Lutz et al, 2017 ; Hirose et al, 2018 ; Costanza et al, 2021 ; Iznak et al, 2021 ; Koenig et al, 2021 ). Lifetime SA was significantly associated with both higher impulsivity and higher aggression ( Costanza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding fNIRS, only one study has examined resting-state activation in youths with NSSI. 46 In addition, cultural differences are believed to be reduced by applying ERT developed and standardized in Korea. This study is expected to contribute to future self-injurious behavior research as the first to investigate the differences in the connectivity of the PFC in Korean adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The study has founded that adolescents with NSSI showed significantly decreased PFC oxygenation compared to HC, as indexed by oxygenated hemoglobin. 59 Second, NSSI behaviour is the result of the interaction of multiple factors; studies should explore the intrinsic mechanisms between different factors. Third, additional large-scale longitudinal studies are necessary to assess the different development trajectories associated with family cumulative risk, such as the relationships between the different development periods of family cumulative risk and NSSI.…”
Section: Discussionmentioning
confidence: 99%